Analisis Yuridis Kesalahan Prosedur Eksekusi Putusan Pengadilan yang Mengakibatkan Kerugian Pihak Ketiga Beriktikad Baik Dalam Kasus Penggusuran di Tambun Selatan - Novita Widia Sari; Lidia Theresia Rotua Simamora; Wijayati W; Dwi Desi Yayi Tarina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
On January 30, 2025, the Cikarang District Court (Pengadilan Negeri/PN Cikarang) carried out a land eviction execution at Cluster Setia Mekar Residence 2, Tambun Selatan, Bekasi Regency, based on the Bekasi District Court Decision Number 128/PDT.G/1996/PN.BKS which had obtained permanent legal force (inkracht van gewijsde). This study aims to analyze two primary legal issues: first, whether the execution conducted by PN Cikarang complied with the applicable civil procedural law, particularly regarding the obligation to coordinate and re-measure land boundaries with the Land Office as interpreted from Article 93 of Government Regulation Number 18 of 2021 in conjunction with Government Regulation Number 24 of 1997; and second, what forms of legal protection are available to good-faith third parties who become victims of erroneous execution over certified immovable property. This research employs a normative juridical method with statutory and case approaches. The findings indicate that the execution was procedurally defective as it was not preceded by coordination and a measurement request to the land authority, thereby violating the principles of legal certainty and publicity in property law. The aggrieved third parties may pursue compensation claims under Articles 1365 and 1366 of the Civil Code, third-party opposition (derden verzet) under Article 195 paragraph (6) of HIR in conjunction with Article 208 of HIR, and reporting to the Judicial Commission.